Management Strategy of Wase Glee in Disaster Mitigation for Sustainable Village Economic Development - Tuti Meutia; Mayang Murni; Muhammad Salman; Nurul Kahfi Lubis; Eva Andriani (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2026)
Forest governance in Aceh has long been supported by customary institutions such as Lembaga Adat Uteuen, yet the operational role of wase glee in disaster mitigation and sustainable village economic development remains underexplored. Previous studies have mainly emphasized the cultural and legal recognition of customary forest systems, with limited attention to how customary economic mechanisms function in disaster risk reduction and local economic governance. This study aims to analyze the management of wase glee as a customary mechanism in disaster mitigation and its potential contribution to sustainable village economic development in East Aceh Regency. This research employed a qualitative descriptive approach in Gampong Sembuang, Serbajadi Subdistrict. Data were collected through observation, semi-structured interviews, and documentation involving customary leaders, village officials, and forest-dependent community members selected through purposive sampling. The data were analyzed using thematic analysis, supported by triangulation to ensure validity. The findings reveal that wase glee has not functioned effectively because customary authority has weakened, formal village regulations are absent, and forest resource utilization has shifted from collective customary control to individual and religious-based practices. Analytically, this decline reflects an institutional transformation in which customary norms have lost their regulatory capacity over forest use, disaster prevention, and collective economic benefit distribution. As a result, forest resources remain weakly supervised, while their potential contribution to ecological risk reduction and village income is unrealized. This study positions wase glee as a potential hybrid governance mechanism integrating local wisdom, community-based disaster risk reduction, and sustainable village economic development.